Does central bank independence really matter? - Haan, Jakob de; Kooi, Willem J. (Journal of Banking & Finance, 2000)
This paper provides a new indicator for central bank independence (CBI) based on the turnover rate of central bank governors for 82 developing countries over the period 1980–1989. Using this new indicator it is concluded that this proxy for CBI is related to inflation, only if the high inflation countries are included in the sample. The view that both CBI and inflation are caused by effective opposition towards inflation is not supported. Using both the extreme bound analysis and Sala-i-Martin's method we do not find evidence that CBI is robustly related to economic growth.